Technology of modified bitumen production for the road construction - Mardupenko, Aleksey; Grigorov, Andrey; Sinkevich, Irina; Tulskaya, Alena (My University, 2019)
In the current article, there has been proposed technology of production of the modified bitumen that is based on the compounding of petroleum residue with solid domestic wastes at 420–470K. The advantages of technology are compactness of technological scheme, simplicity of technological equip-ment, and minimal hazardous emission. There have been obtained laboratory samples with the pro-perties that exceed the properties of commodity bitumen PRB-90/130 (petroleum road bitumen). The produced modified bitumen has expanded temperature range of application, which makes the bitumen universal for any climatic exploitation zone.
Keywords: modified bitumen; oil sludge; polymer wastes; compounding; softening point; fraction; grinding